Identity Politics on Social Media in the 2020 Surabaya Mayoral Election: Narrative Strategies, Public Response, and the Impact of Digital Democratization - Adiba, Sabiella Maris (Internasional Journal of Politics and Public Policy, 2025)
This study aims to explore how identity politics was constructed, disseminated, and received by the public in the context of the 2020 Surabaya mayoral election through social media, particularly Instagram and X (formerly Twitter). The research focuses on how identity narratives were manipulated by candidates and their campaign teams as an electoral strategy, how the public responded to such campaigns, and the socio-political impact on the quality of local democracy. Using a qualitative approach and digital netnography methods, this study analyzes candidates' content, campaign hashtags, and public interactions. The findings reveal that social media became a highly contested arena for identity politics, where religious, regional, and moral narratives were used to shape candidate images and mobilize support. However, these practices also resulted in social polarization, minority exclusion, and limited deliberative space. This study contributes to the discourse on digital democracy and identity politics in the context of local elections in Indonesia.